Effects Of Plyometric Training On C-Reactive Protein (CRP) In Football Players: Preparation From Pre-Season To In-Season - Sajid Mehmood , Dr. Syed Asif Abbas , Muqaddas Niaz , Muhammad Nofal Ishaq , Razia Nawaz (Migration Letters, 2024)
Exercise plays a key role in maintaining physical health by strengthening bones and muscles, regulating metabolism, preventing chronic diseases, and promoting longevity.Objective: The purpose of this study was to examine the effects of a 12-week plyometric training program on C-reactive Protein (CRP) levels in elite male football players from South Punjab, Pakistan, during the pre-season to in-season phase. Methods: A total of 60 male football players aged 18-28 were randomly selected and divided into two equal groups: an experimental group (n = 30), which received the plyometric training, and a control group (n = 30), which did not undergo any specific training. The study utilized a pre-test and post-test experimental design. [1]Blood samples were collected from all participants before and after the intervention to measure CRP levels. The experimental group participated in football-specific plyometric training three times a week for 12 weeks, while the control group followed their routine activities without any training intervention. CRP levels were analyzed using independent t-tests and paired t-tests to assess changes within and between groups. Results: Pre-test results showed no significant difference in CRP levels between the experimental (M = 0.6733) and control groups (M = 0.6733), with a p-value of 1.000. Post-test analysis revealed a significant reduction in CRP levels in the experimental group (M = 0.5867), compared to the control group (M = 0.6767), with a p-value of .005. Additionally, within-group analysis showed a significant decrease in CRP levels in the experimental group from pre-test to post-test (p = .000), whereas no significant change was observed in the control group (p = .745). Conclusion: The findings suggest that a 12-week plyometric training program significantly reduces CRP levels in elite football players, indicating the program's potential to mitigate inflammatory responses during the pre-season to in-season transition. No significant changes were observed in the control group, highlighting the importance of targeted training for improving health markers in athletes.